PENGARUH KUALITAS KEHIDUPAN KERJA DAN SIKAP KERJA TERHADAP KEPUASAN KERJA GURU SMA NEGERI KECAMATAN JEKAN RAYA KOTA PALANGKA RAYA PROVINSI KALIMANTAN TENGAH - MOH KHOIRI, MOH KHOIRI (Faculty of training and education, Pamulang university, 2017)
ABSTRAK Abstract: This study aims to determine the effect of (1) the quality of work life, (2) working attitude, (3) job satisfaction of teachers working SMA Kecamtan Jekan Kingdom city of Palangkaraya , Central Kalimantan Province. In the data analysis, this study used a survey method using a causal analysis technique Strip. This study used a sample of 138 teachers in three high schools in District Jekan Kingdom city of Palangkaraya are selected using Slovin formula.The results showed that : first , there are positive influence between the quality of work life and job satisfaction of teachers in schools . Secondly , there is a positive effect between work attitudes and job satisfaction of teachers in schools . Third , there is a positive effect between the quality of working life and work attitudes of teachers in schools. Keywords: quality of work life, job attitude and job satisfaction